Seroprevalence of Hepatitis B, Hepatitis C, HIV Infections in Blood Donors of Khulna, Bangladesh - Rudra, S; Chakrabarty, P; Hossain, MA; Akter, H; Bhuiyan, MR (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):515-9 The abstract of this article is available on the PubMed website